2004
DOI: 10.1023/b:comh.0000022733.12858.cb
|View full text |Cite
|
Sign up to set email alerts
|

Community Integration in the Early Phase of Housing Among Homeless Persons Diagnosed with Severe Mental Illness: Successes and Challenges

Abstract: The present investigation used qualitative methods to explore the response to housing and experience of community integration of formerly homeless individuals diagnosed with severe mental illness recently housed in both independent and staffed residential settings. Findings indicate that entering into housing after a long period of homelessness is associated with improvements in community integration for most individuals diagnosed with severe mental illness. However, for a meaningful minority, the adaptation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
112
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(124 citation statements)
references
References 13 publications
9
112
0
3
Order By: Relevance
“…When residents perceive their neighborhoods to be unsafe, feelings of danger may overtake their daily lives, causing them to stay isolated in their homes and refuse to reach out to fellow residents (Zeldin and Topitzes 2002). This has deleterious effects on the psychological sense of community, and it appears to be particularly problematic and under-studied among individuals with serious mental illness (Yanos et al 2004;Wong and Solomon 2002). Newman (1994) found that, among individuals with SMI living in Baltimore, Maryland, and Cincinnati and Columbus, OH (80% rented apartments or homes and lived independently, whereas 20% lived rent-free with relatives or friends), concerns about being victimized by neighborhood crime appeared to overwhelm relatively positive reports about other neighborhood characteristics.…”
Section: Neighborhood Safetymentioning
confidence: 99%
“…When residents perceive their neighborhoods to be unsafe, feelings of danger may overtake their daily lives, causing them to stay isolated in their homes and refuse to reach out to fellow residents (Zeldin and Topitzes 2002). This has deleterious effects on the psychological sense of community, and it appears to be particularly problematic and under-studied among individuals with serious mental illness (Yanos et al 2004;Wong and Solomon 2002). Newman (1994) found that, among individuals with SMI living in Baltimore, Maryland, and Cincinnati and Columbus, OH (80% rented apartments or homes and lived independently, whereas 20% lived rent-free with relatives or friends), concerns about being victimized by neighborhood crime appeared to overwhelm relatively positive reports about other neighborhood characteristics.…”
Section: Neighborhood Safetymentioning
confidence: 99%
“…The possibility that stigmatizing attitudes towards people with mental illness varies by neighborhood, and that variation in these attitudes can impact community integration (which Segal et al's [1980]; study implied) also needs to be explicitly examined. Some preliminary research has also suggested that the degree of "fit" between an individual with mental illness and the neighborhood where he or she finds housing, rather than any specific characteristics of the community per se, is the most important factor in determining community integration (Yanos, Barrow, and Tsemberis, 2004), but this hypothesis needs to be studied further.…”
Section: The Move Toward Scatter-site Independent Housingmentioning
confidence: 99%
“…16,17,19 In addition to these outcomes, the Canadian multisite trial includes measures of community integration, recovery, and quality of life. Instruments for the larger study were chosen based on a consensus measurement framework and specific literature reviews for validated instruments.…”
Section: Introductionmentioning
confidence: 99%